2019
DOI: 10.5860/rbm.20.2.95
|View full text |Cite
|
Sign up to set email alerts
|

An Independent Study Course by an Academic Library Department: Teaching with the Gems of Special Collections

Abstract: Special collections in academic libraries provide rich learning environments for student engagement. This article describes the introduction of an independent study course by an academic library department as a high-impact educational practice supporting undergraduate research. Under the supervision of the faculty archivist, the student in this study was challenged to discover and research “gems,” unusual or significant items, on a topic of her choosing. She selected three works related to James Joyce’s Finneg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…, special collections have "usefulness for teaching and learning (particularly through the development of critical thinking skills)" (p. 11). In her work,Silva (2019) describes creating and teaching with special collections through an independent studies class. In this case, Silva found that "independent study courses present unique opportunities for undergraduate student research" (p. 112).…”
mentioning
confidence: 99%
“…, special collections have "usefulness for teaching and learning (particularly through the development of critical thinking skills)" (p. 11). In her work,Silva (2019) describes creating and teaching with special collections through an independent studies class. In this case, Silva found that "independent study courses present unique opportunities for undergraduate student research" (p. 112).…”
mentioning
confidence: 99%